Rongalite as a C1 source: sulfonylmethylation of indoles with aryl/alkyl hydrazides and sulfinates - Kale, Someshwar B.; Patil, Tejaswini A.; Das, Utpal (Journal of Organic Chemistry, 2024)
Herein, we present a sulfonylmethylation of indoles with aryl/alkyl hydrazides and sulfinates that provides viable access to sulfone compounds using rongalite as a C1 source. This protocol features readily available chemicals and simple operations, and the products were obtained in moderate to good yields.